Endoscopic full-thickness resection in the colorectum with a novel over-the-scope device: first experience - Schmidt, Arthur; Bauerfeind, Peter; Gubler, Christoph; Damm, Michael; Bauder, Markus; Caca, Karel (Endoscopy, 2015)
Background and study aims: Endoscopic full-thickness resection (EFTR) in the lower gastrointestinal tract may be a valuable therapeutic and diagnostic approach for a variety of indications. Although feasibility of EFTR has been demonstrated, there is a lack of safe and effective endoscopic devices for routine use. The aim of this study was to investigate the efficacy and safety of a novel over-the-scope device for colorectal EFTR.Patients and methods: Between July 2012 and July 2014, 25 patients underwent EFTR at two tertiary referral centers. All resections were performed using the full-thickness resection device (FTRD; Ovesco Endoscopy, Tübingen, Germany). Data were collected retrospectively.Results: Indications for EFTR were: recurrent or incompletely resected adenoma with nonlifting sign (n = 11), untreated adenoma and nonlifting sign (n = 2), adenoma involving the appendix (n = 5), flat adenoma in a patient with coagulopathy (n = 1), diagnostic re-resection after incomplete resection of a T1 carcinoma (n = 2), adenoma involving a diverticulum (n = 1), submucosal tumor (n = 2), and diagnostic resection in a patient with suspected Hirschsprung’s disease (n = 1). In one patient, the lesion could not be reached because of a sigmoid stenosis. In the other patients, resection of the lesion was macroscopically complete and en bloc in 20/24 patients (83.3 %). The mean diameter of the resection specimen was 24 mm (range 12 – 40 mm). The R0 resection rate was 75.0 % (18/24), and full-thickness resection was histologically confirmed in 87.5 %. No perforations or major bleeding were observed during or after resection. Two patients developed postpolypectomy syndrome, which was managed with antibiotic therapy.Conclusions: Full-thickness resection in the lower gastrointestinal tract with the novel FTRD was feasible and effective. Prospective studies are needed to further evaluate the device and technique.